Pengaruh Iklim Komunikasi Organisasi dan Tingkat Kepuasan Kerja Terhadap Tingkat Kinerja Karyawan Pasca Merger di PT. Tumbakmas Niagasakti Cabang Semarang - Winardiani, Merrlintya Ayu (Interaksi: Jurnal Ilmu Komunikasi, 2015)
Abstract:Performance of a company was influenced by a number of important aspects includedcommunication. Continuous communication that existed within a company will gradually establishan organizational communication climate. Basically, humans live and work wish a steadiness, settle,welfare, and satisfaction. The purpose of this study was to determine and explained the positiverelationship of organizational communication climate, work satisfaction, the level of performanceof the post-merger company. The results showed that the variables of organizational communicationclimate and work satisfaction levels jointly affected the level of employee performance. While thepartial test showed that variables of organizational communication climate affected larger on thelevel of employee performance.